2015
DOI: 10.1186/s40807-015-0018-9
|View full text |Cite
|
Sign up to set email alerts
|

Time series decomposition model for accurate wind speed forecast

Abstract: Climate change can be considered to be the greatest environmental challenge our world is facing today. Along with the need to ensure long-term assurance of energy supply, it imposes an obligation on all of us to consider ways of reducing our carbon footprint and sourcing more of our energy from renewable sources. Wind energy is one such source and forecasting methods for the prediction of wind speed are becoming increasingly significant due to the penetration of wind power as an alternative to conventional ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 15 publications
0
25
0
8
Order By: Relevance
“…For instance, Prema and Rao applied Holt-Winters, ARIMA and time series decomposition methods, and they found 28.63%, 23.26%, 18.24% MAPE', respectively. They also mentioned that 30% MAPE is acceptable by the Government of India [37]. We found MAPE for the time series decomposition, Holt-Winters and ARIMA methods at 19%, 14% and 12.9% respectively.…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…For instance, Prema and Rao applied Holt-Winters, ARIMA and time series decomposition methods, and they found 28.63%, 23.26%, 18.24% MAPE', respectively. They also mentioned that 30% MAPE is acceptable by the Government of India [37]. We found MAPE for the time series decomposition, Holt-Winters and ARIMA methods at 19%, 14% and 12.9% respectively.…”
Section: Resultsmentioning
confidence: 73%
“…They found that the most significant part in the accuracy of forecasting is the seasonal decomposition method of the time series. Prema and Rao forecasted wind speed using time series decomposition, exponential smoothing and back propagation neural networks [37]. They observed that decomposition of time series and ARIMA methods gave more accurate results.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations